Knowledge management librarians: Evolving competencies in knowledge capture and dissemination in an academic environment - Hassan, Basri; Abdullah, Sarifah; Albert, Geeta; Ibrahim, Nor Takrim; Goh, See Kwong (IFLA, 2018)
In this paper, we examine the roles and responsibilities of Knowledge Management (KM) librarians in a University and outline the skills and knowledge to illuminate and maximize the possibilities of the position, to provide new content in new mediums to an increasingly discerning user community. This relatively new position is being created as libraries strive to manage collaborative knowledge management technologies, upgrade the service model in reference, in particular enhancing the skills of ‘liaison officers’ when engaging with their patrons’ point-of-need preferences at their site, quality of knowledge, device choice, and their knowledge sharing and seeking behavior. We draw upon our own experiences in implementing a virtual knowledge sharing community in the International Islamic University Malaysia (IIUM) as well as referring to the latest literature on the topic. Our three-year implementation journey encompassing unforeseen problems and discussions in building workarounds, in how best to manage tacit knowledge amongst academic and non-academic staff, provided valuable insights, focusing in particular on KM training for all librarians, the development of an ‘unofficial’ knowledge management implementation curriculum (KMIC) and the formation of the IIUM KM Task Force to sustain KM initiatives in the academia.